Preparation method of copper-clad ceramic substrate

By printing a mixed slurry of polyimide liquid resin and nitrate on copper foil, using high-temperature nitrate decomposition to provide oxygen, the problems of uneven oxide layer of copper-clad ceramic substrate and complex process are solved, and the peel strength of the substrate is improved and thermal conductivity meet the needs of high-performance substrates.

CN119191867APending Publication Date: 2024-12-27NANYANG JINGUAN ELECTRIC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411363116.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing copper-clad ceramic substrate preparation methods have complex and complicated problems in the oxidation process of copper foil and uneven oxide layers, which is difficult to meet the market demand for high-performance substrates.

Method used

The mixed slurry of polyimide liquid resin and nitrate is formed on the copper foil through screen printing process, and the nitrate decomposition at high temperature provides quantitative oxygen for oxidation reaction, combining with hot pressing method to enhance adhesion and Uniformity.

Benefits of technology

The uniformity of the oxide layer and the simplicity of the process are achieved, the peel strength and thermal conductivity of the copper-clad ceramic substrate are improved, the complexity of the oxidation process is reduced, and the process window is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of copper-clad ceramic substrates, and provides a preparation method of a copper-clad ceramic substrate, and the preparation method of the copper-clad ceramic substrate comprises the following steps: S1, uniformly mixing polyimide liquid resin and nitrate to obtain slurry; s2, performing copper reduction treatment on the copper foil; s3, printing the slurry on a copper foil, and laminating an aluminum oxide ceramic substrate with the copper foil to obtain a copper-clad ceramic substrate; the mass ratio of the polyimide liquid resin to the nitrate is (5-15): 1. According to the technical scheme, the problems that in the prior art, a preparation method of the copper-clad ceramic substrate is complex and tedious, and an oxide layer is not uniform are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-clad ceramic substrates, and in particular to a preparation method of a copper-clad ceramic substrate. Background Art

[0002] In today's new energy, rail transportation, semiconductor refrigeration and other fields, the demand for high-performance substrates is growing. Copper-clad ceramic substrates are an advanced composite substrate that is directly combined with the surface of alumina ceramic substrates by hot-melt bonding at high temperatures. Because they can be made of thick copper and have a large current carrying capacity, they have been widely used.

[0003] The process of copper-clad ceramic substrate is mainly divided into two stages. The first stage is that copper reacts with oxygen to generate cuprous oxide. In this stage, the oxygen content needs to be precisely controlled to prevent excessive oxygen from generating cupric oxide. The second stage is that the cuprous oxide on the surface of the copper foil forms a eutectic liquid phase with the alumina ceramic, thereby forming a bond.

[0004] At present, the existing copper foil oxidation schemes mainly include dry oxidation and wet oxidation. Dry oxidation is to oxidize in the temperature range of 600~750℃, with precise control of oxygen partial pressure to ensure that the oxidizing component is cuprous oxide. However, this scheme is difficult to ensure the uniformity of oxygen distribution in the furnace, which is prone to cause local uneven oxidation, and then bubbles are generated at the interface during sintering; wet oxidation is to oxidize by immersing the copper foil in an acidic or alkaline oxidizing solution. This scheme has high requirements for the adequacy of the circulation of the oxidizing solution in the tank, and single-sided protection is required at the same time, which is more cumbersome in process. Therefore, the existing preparation method of copper-clad ceramic substrates has certain technical difficulties in the copper foil oxidation link, and a simpler, more efficient and highly uniform oxide layer technical solution is needed to meet the growing market demand. Summary of the invention

[0005] The invention provides a method for preparing a copper-clad ceramic substrate, which solves the problems of complicated and cumbersome preparation methods and uneven oxide layers in the related art.

[0006] The technical solution of the present invention is as follows: The present invention provides a method for preparing a copper-clad ceramic substrate, comprising the following steps: S1, mixing polyimide liquid resin and nitrate evenly to obtain slurry; S2, reducing the copper foil; S3, printing the slurry on the copper foil, laminating the alumina ceramic substrate and the copper foil to obtain a copper-clad ceramic substrate; The mass ratio of the polyimide liquid resin to the nitrate is 5-15:1.

[0007] As a further technical solution, the mass ratio of the polyimide liquid resin to the nitrate is 7-9:1.

[0008] As a further technical solution, the mass ratio of the polyimide liquid resin to the nitrate is 8:1.

[0009] As a further technical solution, the nitrate includes one or both of copper nitrate and aluminum nitrate.

[0010] As a further technical solution, the polyimide liquid resin consists of a first polyimide liquid resin and a second polyimide liquid resin, and the first polyimide liquid resin and the second polyimide liquid resin have different glass transition temperatures.

[0011] As a further technical solution, the glass transition temperature of the first polyimide liquid resin is 272° C., the glass transition temperature of the second polyimide liquid resin is 385° C., and the mass ratio of the first polyimide liquid resin to the second polyimide liquid resin is 1-3:1.

[0012] As a further technical solution, the mass ratio of the first polyimide liquid resin to the second polyimide liquid resin is 5:3.

[0013] As a further technical solution, the slurry also includes a solvent, a leveling agent, a dispersant, and a defoaming agent. In parts by weight, the slurry includes the following raw materials: 50 to 150 parts of polyimide liquid resin, 10 parts of nitrate, 10 to 15 parts of solvent, 0.5 to 1.5 parts of leveling agent, 0.5 to 1 part of dispersant, and 0.5 to 0.8 parts of defoaming agent.

[0014] As a further technical solution, the solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.

[0015] As a further technical solution, the leveling agent includes one or two of BYK-358N and BYK-361N.

[0016] As a further technical solution, the dispersant includes one or more of BYK-151, BYK-154, and BYK-155.

[0017] As a further technical solution, the defoaming agent includes one or more of a polydimethylsiloxane defoaming agent, a polyether-modified silicon defoaming agent, and a mineral oil defoaming agent.

[0018] As a further technical solution, the abrasive particle size specification used in the copper reduction treatment is ceramic 600 mesh to 1000 mesh.

[0019] As a further technical solution, the lamination method is a hot pressing method.

[0020] As a further technical solution, the slurry is printed with a thickness of 10-20 μm.

[0021] As a further technical solution, the thickness of the alumina ceramic substrate is 0.25-0.5 mm, and the thickness of the copper foil after copper reduction is 50-70 μm.

[0022] The present invention uses two polyimide liquid resins with different glass transition temperatures as raw materials, which work together to further enhance the adhesion between the ceramic substrate and the copper foil, improve the dispersibility of the slurry, increase the uniformity of the oxide layer, and improve the peel strength and thermal conductivity of the copper-clad ceramic substrate.

[0023] In the present invention, by regulating the mass ratio of polyimide liquid resin and nitrate, the thickness of the oxide layer is accurately controlled, the oxidation reaction rate is adjusted, and the uniformity of the oxide layer is improved, so that the oxidation process is easier to control, and the best oxidation effect and the simplest preparation process are achieved.

[0024] The working principle and beneficial effects of the present invention are: In the present invention, a polyimide liquid resin and a nitrate are mixed to prepare a slurry, a certain amount of the nitrate slurry is printed on a copper foil by a screen printing process, and a certain amount of oxygen is provided to the copper foil for oxidation reaction by a method of decomposing the nitrate at a high temperature, thereby generating an oxide layer with uniform thickness, reducing the complexity of the oxidation process, and obtaining a uniform oxide layer without strictly controlling the oxygen partial pressure in the oxidation furnace, thereby having a wider process window and being easier to control, and the obtained copper-clad ceramic substrate has high peeling strength and good thermal conductivity. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the following examples and comparative examples: The first polyimide liquid resin: the glass transition temperature is 272°C, the manufacturer is Dongguan Shengbang Polymer Materials Co., Ltd.; The second polyimide liquid resin: the glass transition temperature is 385°C, the manufacturer is Dongguan Zhanyang Polymer Materials Co., Ltd.; Bisphenol A type liquid epoxy resin: model E51; Liquid phenolic resin: model 2127; Polydimethylsiloxane defoamer: solid content is 20%; Polyether modified silicon defoamer: model THIX-299, manufacturer: Yantai Hengxin Chemical Technology Co., Ltd. Mineral oil defoamer: model TY-111; The thickness of the alumina ceramic substrate is 0.3 mm, and the thickness of the copper foil after copper reduction is 50 μm.

[0027] Example 1 S1, weigh 50 parts of the first polyimide liquid resin, 10 parts of copper nitrate, 10 parts of N,N-dimethylformamide, 0.5 parts of BYK-358N, 0.5 parts of BYK-151, and 0.5 parts of polydimethylsiloxane defoamer, mix and stir evenly to obtain a slurry; S2. Use a ceramic 600-mesh brush wheel to clean the copper foil and perform copper reduction treatment; S3. Print the slurry on the copper foil by screen printing process. The thickness of the slurry printing is 10 μm. The ceramic substrate and the copper foil are laminated and hot pressed. The hot pressing temperature is 300° C., the pressure is 5 MPa, and the hot pressing time is 60 min. After cooling, the copper-clad ceramic substrate is obtained.

[0028] Example 2 S1. Weigh 100 parts of the first polyimide liquid resin, 10 parts of copper nitrate, 12 parts of N,N-dimethylacetamide, 1 part of BYK-358N, 0.8 parts of BYK-154, and 0.7 parts of a polyether-modified silicon defoamer, mix and stir evenly to obtain a slurry; S2. Use a ceramic 800-mesh brush wheel to clean the copper foil and perform copper reduction treatment; S3. Print the slurry on the copper foil by screen printing process. The thickness of the slurry printing is 10 μm. The ceramic substrate and the copper foil are laminated and hot pressed. The hot pressing temperature is 325° C., the pressure is 6 MPa, and the hot pressing time is 75 min. After cooling, the copper-clad ceramic substrate is obtained.

[0029] Example 3 S1. Weigh 150 parts of the first polyimide liquid resin, 10 parts of copper nitrate, 15 parts of N,N-dimethylformamide, 1.5 parts of BYK-361N, 0.8 parts of BYK-155, and 0.8 parts of a mineral oil defoamer, mix and stir evenly to obtain a slurry; S2. Clean the copper foil with a ceramic 1000 mesh brush wheel to reduce copper; S3. Print the slurry on the copper foil by screen printing process. The thickness of the slurry printing is 10 μm. The ceramic substrate and the copper foil are laminated and hot pressed. The hot pressing temperature is 350° C., the pressure is 7 MPa, and the hot pressing time is 90 min. After cooling, the copper-clad ceramic substrate is obtained.

[0030] Example 4 Compared with Example 3, Example 4 is different in that 150 parts of the first polyimide liquid resin are replaced with 70 parts of the first polyimide liquid resin.

[0031] Example 5 Compared with Example 3, Example 5 is different in that 150 parts of the first polyimide liquid resin are replaced with 80 parts of the first polyimide liquid resin.

[0032] Example 6 Compared with Example 3, Example 6 is different in that 150 parts of the first polyimide liquid resin are replaced with 90 parts of the first polyimide liquid resin.

[0033] Example 7 Compared with Example 3, Example 7 is different in that 150 parts of the first polyimide liquid resin are replaced with 100 parts of the first polyimide liquid resin.

[0034] Example 8 Compared with Example 5, Example 8 is different in that 80 parts of the first polyimide liquid resin are replaced with an equal amount of the second polyimide liquid resin.

[0035] Example 9 Compared with Example 5, Example 9 is different in that 80 parts of the first polyimide liquid resin are replaced by 30 parts of the first polyimide liquid resin and 50 parts of the second polyimide liquid resin.

[0036] Example 10 Compared with Example 5, Example 10 is different in that 80 parts of the first polyimide liquid resin are replaced by 40 parts of the first polyimide liquid resin and 40 parts of the second polyimide liquid resin.

[0037] Embodiment 11 Compared with Example 5, Example 11 is different in that 80 parts of the first polyimide liquid resin are replaced by 50 parts of the first polyimide liquid resin and 30 parts of the second polyimide liquid resin.

[0038] Example 12 Compared with Example 5, Example 12 is different in that 80 parts of the first polyimide liquid resin are replaced by 60 parts of the first polyimide liquid resin and 20 parts of the second polyimide liquid resin.

[0039] Embodiment 13 Compared with Example 5, Example 13 is different in that 80 parts of the first polyimide liquid resin are replaced by 70 parts of the first polyimide liquid resin and 10 parts of the second polyimide liquid resin.

[0040] Comparative Example 1 Compared with Example 3, Comparative Example 1 is different in that only copper nitrate is added.

[0041] Comparative Example 2 Compared with Example 3, the difference of Comparative Example 2 is that 150 parts of the first polyimide liquid resin are replaced by an equal amount of bisphenol A type liquid epoxy resin.

[0042] Comparative Example 3 Compared with Example 3, the difference of Comparative Example 3 is that 150 parts of the first polyimide liquid resin are replaced by an equal amount of liquid phenolic resin.

[0043] The copper-clad ceramic substrates prepared in Examples 1 to 13 and Comparative Examples 1 to 3 were tested according to the following method: 1. Peel strength: Test the peel strength of the sample according to the test method specified in GB / T 4722-2017 "Test methods for rigid copper-clad laminates for printed circuits".

[0044] 2. Thermal expansion coefficient: Use Diamond static thermomechanical analyzer to test the thermal expansion coefficient of copper-clad ceramic substrate.

[0045] The test results are shown in the following table: Table 1 Performance test results of copper-clad ceramic substrates prepared in Examples 1 to 13 and Comparative Examples 1 to 3

[0046] Compared with Comparative Example 1, Example 3 simultaneously adds the first polyimide liquid resin and copper nitrate. Compared with Comparative Examples 2 and 3, the resin added in Example 3 is the first polyimide liquid resin. As a result, the peel strength of Example 3 is better than that of Comparative Examples 1 to 3, and the thermal expansion coefficient is lower than that of Comparative Examples 1 to 3, indicating that the first polyimide liquid resin and copper nitrate play a synergistic role, which can enhance the peel strength of the copper-clad ceramic substrate and reduce the thermal expansion coefficient of the copper-clad ceramic substrate. Examples 3 to 7 add the first polyimide liquid resin and copper nitrate in different mass ratios. As a result, the peel strength of Examples 4 to 6 is better than that of Examples 3 and 7, and the thermal expansion coefficient is less than that of Examples 3 and 7, indicating that when the mass ratio of the first polyimide liquid resin to copper nitrate is 7 to 9:1, and the preferred ratio is 8:1, the peel strength and thermal expansion coefficient of the obtained copper-clad ceramic substrate are better.

[0047] Compared with Examples 5 and 8, Examples 9 to 13 simultaneously add the first polyimide liquid resin and the second polyimide liquid resin. As a result, the peel strength of Examples 9 to 13 is better than that of Examples 5 and 8, and the thermal expansion coefficient is less than that of Examples 5 and 8, indicating that the first polyimide liquid resin and the second polyimide liquid resin play a synergistic role, which can improve the peel strength of the copper-clad ceramic substrate and reduce the thermal expansion coefficient of the copper-clad ceramic substrate. In Examples 9 to 13, the first polyimide liquid resin and the second polyimide liquid resin are added in different mass ratios. As a result, the peel strength of Examples 10 to 12 is better than that of Examples 9 and 13, and the thermal expansion coefficient is less than that of Examples 9 and 13, indicating that when the mass ratio of the first polyimide liquid resin to the second polyimide liquid resin is 1 to 3:1, and the preferred ratio is 5:3, the peel strength and thermal expansion coefficient of the obtained copper-clad ceramic substrate are optimal.

[0048] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a copper-clad ceramic substrate, characterized in that: The following steps are involved: S1, mixing polyimide liquid resin and nitrate evenly to obtain slurry; S2, reducing the copper foil; S3, printing the slurry on the copper foil, laminating the alumina ceramic substrate and the copper foil to obtain a copper-clad ceramic substrate; The mass ratio of the polyimide liquid resin to the nitrate is 5-15:

1.

2. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: The polyimide liquid resin consists of a first polyimide liquid resin and a second polyimide liquid resin, and the first polyimide liquid resin and the second polyimide liquid resin have different glass transition temperatures.

3. The method for preparing a copper-clad ceramic substrate according to claim 2, characterized in that: The glass transition temperature of the first polyimide liquid resin is 272° C., the glass transition temperature of the second polyimide liquid resin is 385° C., and the mass ratio of the first polyimide liquid resin to the second polyimide liquid resin is 1-3:

1.

4. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: The slurry also includes a solvent, a leveling agent, a dispersant, and a defoaming agent. In parts by weight, the slurry includes the following raw materials: 50-150 parts of polyimide liquid resin, 10 parts of nitrate, 10-15 parts of solvent, 0.5-1.5 parts of leveling agent, 0.5-1 part of dispersant, and 0.5-0.8 part of defoaming agent.

5. The method for preparing a copper-clad ceramic substrate according to claim 4, characterized in that: The solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.

6. The method for preparing a copper-clad ceramic substrate according to claim 4, characterized in that: The leveling agent includes one or both of BYK-358N and BYK-361N.

7. The method for preparing a copper-clad ceramic substrate according to claim 4, characterized in that: The dispersant includes one or more of BYK-151, BYK-154, and BYK-155.

8. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: The defoaming agent includes one or more of polydimethylsiloxane defoaming agent, polyether modified silicon defoaming agent and mineral oil defoaming agent.

9. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: The abrasive particle size specification used in the copper reduction treatment is ceramic 600 mesh to 1000 mesh.

10. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: The laminating method is a hot pressing method.

Citation Information

Patent Citations

  • Preparation method of aluminium nitride base ceramic copper-clad plate

    CN103819215A

  • A preparing method of a ceramic copper-clad plate

    CN104072186A

  • Preparation method of copper clad substrate

    CN107474724A

  • Glue discharging and sintering integrated kiln

    CN215113873U

  • USE OF CERTAIN PLATELINE ACCUMULATOR PLANTS FOR CARRYING OUT ORGANIC CHEMISTRY REACTIONS

    FR3008323A1